Zika: an old virus with a new face - Avšic Županc Tatjana; Petrovec Miroslav (Slovenian Journal of Public Health, 2016)
Zika virus is a mosquito-borne flavivirus that represents a public health emergency at the ongoing epidemic. This obscure virus was limited to sporadic cases in Africa and Asia, until the emergence of Zika virus in Brazil in 2015, when it rapidly spread throughout the Americas. Most Zika virus infections are subclinical or characterized by mild febrile illness. However, neurological complications, including Guillain-Barré syndrome in adults, and congenital anomalies, including microcephaly in babies born to infected mothers, raised a grave concern. Currently, there is no specific antiviral treatment or vaccine available for Zika virus infection. Thus, international public health response is primarily focused on preventing infection, particularly in pregnant women, and on providing up-to-date recommendations to reduce the risk of non-vector transmission of Zika virus.